Analisis Media Loose Part untuk Meningkatkan Kreativitas Anak Usia Dini pada Kelompok B (5-6 Tahun) TK Kristen 1 Satya Wacana Salatiga - Jufitri Jufitri; Fian Rubiyanti; Fika Dewi Musfiati; Ghilba Yuliana Fathna; Maiya Arisca Aminingtyas (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2025)
Every child has the potential to be creative. In the context of education, creativity can be fostered by providing early-age stimulation through activities appropriate to the child’s developmental stage. Their creative abilities can develop optimally. However, in practice, many children’s play activities are still focused on worksheets, resulting in a learning process that is less engaging and tends to be boring. The learning approach using loose parts media is a teaching method that utilizes natural materials found around us that can be separated and combined into a whole, can be aligned, easily blended with other materials, and are practical for carrying and moving. This research uses a qualitative approach with a descriptive qualitative type. The research subjects are the group B children at the Cristian Kindergarten 1 Satya Wacana Salatiga, using data condensation, data display, and conclusion drawing/verification analysis. The results of the study indicate that loose parts media can enhance creativity in early childhood. When children are provided with a variety of play materials, they can realize their creative ideas, imagination, and stimulate their curiosity.